Elucidation of the monoclonal antibody 5G8-reactive, virulence-associated lipopolysaccharide epitope of Haemophilus influenzae and its role in bacterial resistance to complement-mediated killing. - Griffin, R; Cox, A; Makepeace, K; Richards, J; Moxon, E; Hood, D (2005)
The phase-variable locus lex2 is required for expression of a Haemophilus influenzae lipopolysaccharide (LPS) epitope of previously unknown structure. This epitope, which is reactive with monoclonal antibody (MAb) 5G8, has been associated with virulence of type b strains. When strain RM118 (from the same source as strain Rd), in which the lex2 locus and MAb 5G8 reactivity are absent, was transformed with lex2 DNA, transformants that were reactive with MAb 5G8 were obtained. Surprisingly, the 5G8 reactivity of these transformants was phase variable, although the lex2 locus lacked tetrameric repeats and was constitutively expressed. This phase variation was shown to be the result of phase-variable expression of phosphorylcholine (PCho) such that MAb 5G8 reacted only in the absence of PCho. Structural analysis showed that, compared to RM118, the lex2 transformant had acquired a tetrasaccharide, Gal-alpha1,4-Gal-beta1,4-Glc-beta1,4-Glc-beta1,4, linked to the proximal heptose (HepI). A terminal GalNAc was detected in a minority of glycoforms. LPS derived from a mutant of RM7004, a virulent type b strain which naturally expresses lex2 and has LPS containing the same tetrasaccharide linked to HepI as the sole oligosaccharide extension from the inner core, confirmed that GalNAc is not a part of the MAb 5G8-reactive epitope. Thus, MAb 5G8 specifically binds to the structure Gal-alpha1,4-Gal-beta1,4-Glc-beta1,4-Glc-beta attached via a 1,4 linkage to HepI of H. influenzae LPS, and we show that the ability to synthesize this novel tetrasaccharide was associated with enhanced bacterial resistance to complement-mediated killing.